A New Formula for Groundwater Recharge Estimation in Yola, Nigeria - Umaru, A. B.; Lukman, S.; Oke, I. A.; Umara, B. G. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
In this paper,relationship between rainfall and groundwater recharge estimation was evaluated. A standard numerical formula that relates rainfall to groundwater recharge estimation was proposed with the aim of providing error-free groundwater estimate from rainfall. Rainfalls measured in a selected location in Yola, Nigeria and standard formula were used to fix the constants (A,B and c) in the new numerical formula using Microsoft Excel Solver. The constants were used to establish new numerical formula. The new numerical formula was used to estimate groundwater recharge from the rainfall. The accuracy of the new numerical formula was evaluated statistically using Analysis of Variance (ANOVA), relative error; the degree of accuracy, numerical reliability, Model of Selection Criterion (MSC) and Akaike Information Criterion (AIC) and compared with the previous formulae in use for field groundwater recharge estimation with Uttar Pradesh (UP) as the reference value of groundwater recharge. The study revealed that groundwater recharge estimated using the formula was similar to groundwater recharge estimated using standard formulae (UP, Modified Chaturvedi, Kumar and Seethapathi and Rao). In all cases there were significant differences between the groundwater recharge estimated using all the formulae. The new formula provided the lowest relative error of 0.887%, the highest MSC of 4.911; the degree of accuracy of 99.113 % and the lowest AIC of 436.306. The accuracy of the formulae was in the order of new formula greater than Chaturvedi formula greater than Kumar and Seethapathi formula greater than Rao formula. It was concluded that modelling of groundwater recharge using the numerical formula is a promising tool for estimating groundwater recharge with minimum error in water resources management.